Đặc điểm đứt gẫy hoạt động vỡ tai biến xói lở bờ biển vùng Duyên Hải Nam Trung Bộ - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2008)
The characteristics of active faults and the erosion hazard at the South Central Vietnam coast